Simulasi Reinforcement Learning untuk Kecerdasan Buatan pada Exergame Penurun Berat Badan - Sofy Fitriani; Siti Dwi Setiarini; Eddy Bambang Soewono (STMIK Budi Darma, 2022)
The pandemic of Coronavirus Disease 2019 (Covid-19) is still sweeping the globe. This is alarming, and it has a negative impact on physical activity outside the home. Weight gain is one of the issues that has arisen. Artificial intelligence simulation research is proposed for physical activity to help lose weight for it to be something fun with all its limitations. This simulation is going to be included in the game. This study focused on the physical activity carried out based on the results of artificial intelligence calculations to lose weight before being applied to the game. The approach is quantitative. To begin, conduct a literature review to determine the topic, machine learning methods, and calorie calculations for weight loss. Additionally, using reinforcement learning, a model for calculating the need is created for a caloric deficit. The waterfall method is used to model the calculation, which is then simulated in the system. The final stage is model validation, which involves utilizing the functionality correctness in accordance with system requirements. It produces 100 percent correct output based on the list of requirements, according to the tests that have been conducted.